APPLICATION OF CONTENT DIFFERENTIATION LEARNING TO IMPROVE LEARNING OUTCOMES OF CLASS V STUDENTS ON TUBE BUILDING MATERIALS - Kristanti, Yohana (Journal of Elementary Education, 2024)
Implementing learning through a differentiation approach is an adjustment effort made by teachers to meet the different learning needs of students. Differentiation learning is very necessary to support various characteristics of students. The application of differentiation learning is divided into 3, content differentiation, process differentiation and product differentiation, where researchers apply content differentiation to improve student learning outcomes in mathematics learning to build curved sided spaces in the form of tubes. The type of research used is Classroom Action Research (PTK) with II cycles. This PTK is carried out through four stages, namely planning, implementation, observation and reflection. This research was conducted at SDN Sememi II Surabaya. The instruments used in this research are teaching modules and observation sheets, content differentiation is made with 3 levels which are adjusted to the characteristics of students, namely low, medium and high in capturing learning material, this content differentiation is presented in visual form such as books, audio video power points , and kinesthetic. The results of this research show that student learning outcomes have increased. In cycle I, students obtained a completion percentage of 55% or 11 students, where students were still unable to determine the net of the tube correctly and calculate the area of ​​the tube, out of 20 students who had achieved completeness with an average score. -average 64.60. In cycle II, the percentage of completeness increased to 95% or 19 students, were able to determine tube nets, calculate the area and make tubes, out of 20 students who achieved completeness with an average score of 84. Based on the research results it can be concluded that the application of content differentiation in tube building material can improve student learning outcomes.